Conceptual Framework for Partial Invalidity of a Contract (comparative analytical study) - Mohammed Hussein, Researcher. Zainab; Siwan Atwan , Prof. Dr. Raed (Basra studies journal, 2024)
The absence of any pillars of the contract, such as consent, subject matter, or reason, leads to the invalidity of the contract, then the invalidity of the entire contract. However, the contract may be defective in part of it, or it may be invalid in part of it, and some of it may be subject to the arrangement of the effect of the contract on it, and others may not be capable of that, such as the conjunction of a contract. If a gift is made on an unlawful condition, the condition is void and the gift remains valid, unless the condition is the motive for the contract, in which case the entire contract is invalid. Partial invalidation is tantamount to correcting the contract, as it leads to the removal of invalidity from the contract and the preservation of the correct part of it, without changing the legal condition of the contract. Acts of partial invalidity of the contract must be subject to physical and legal division, as well as the possibility of personal division. This means that the contract must be divisible from the point of view of the contracting parties. Partial invalidation actions must also be the invalid part that should not be the motive driving of the contract. So there is no room for applying partial invalidity of the contract if the invalid part was the motivating motive for the contract and the contract is completely invalid.